2023
DOI: 10.21037/jgo-23-6
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of PUM1 by miR-218-5p promotes colorectal tumor-initiating cell properties and tumorigenesis by regulating the PI3K/AKT axis

Abstract: Background: Colorectal cancer (CRC) is the third most common cancer and the fourth most common cause of cancer-related death worldwide. Advanced stage CRC, during the recent past, had a dismal prognosis and only a few available treatments. Pumilio homologous protein 1 (PUM1) is reportedly aberrant in human malignancies, including CRC. However, the role of PUM1 in the regulation of tumor-initiating cells (T-ICs) remains unknown. Methods: The levels of messenger RNAs (mRNAs) were determined by quantitative rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In recent years, miRNA has emerged as a prominent area of research within the field of malignant tumors. As a group of non-coding siRNA, it CRC is a prevalent malignancy affecting the digestive system, specifically the colon or rectum, with high morbidity and mortality [6] . The prevalence of CRC is progressively increasing in our country due to the exacerbation of the aging issue and the alteration of individual's lifestyle patterns.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, miRNA has emerged as a prominent area of research within the field of malignant tumors. As a group of non-coding siRNA, it CRC is a prevalent malignancy affecting the digestive system, specifically the colon or rectum, with high morbidity and mortality [6] . The prevalence of CRC is progressively increasing in our country due to the exacerbation of the aging issue and the alteration of individual's lifestyle patterns.…”
Section: Resultsmentioning
confidence: 99%
“… 1 Colorectal cancer (CRC) is the third most prevalent form of malignant tumor and the leading cause of cancer‐related mortalities worldwide. 2 Colorectal cancers have hypoxic areas, as in several other solid tumors. 3 Several inhibitors that target hypoxic tumor cells have been developed because growing amounts of data have shown that numerous factors, such as hypoxia‐inducible factor 1 alpha (HIF‐1α), are crucial for the survival, angiogenesis, invasion, and invasion and metastasis of hypoxic tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Solid tumors frequently exhibit hypoxia, which enhances the progression and development of many types of cancer 1 . Colorectal cancer (CRC) is the third most prevalent form of malignant tumor and the leading cause of cancer‐related mortalities worldwide 2 . Colorectal cancers have hypoxic areas, as in several other solid tumors 3 .…”
Section: Introductionmentioning
confidence: 99%